TINGKAT KEPUASAN PASIEN PENGGUNA JAMINAN SOSIAL KESEHATAN DI RSUD UMBU RARA MEHA WAINGAPU - YOSEPHINA E.S. GUNAWAN; FICRAM ACHMAD (Poltekkes Kemenkes Kupang, 2016)
Introduction: social security governing body (BPJS) accommodate the Health program health services in one integrated healthcare system, but in practice, people are quite confused and difficult in following the enactment of the administration by the BPJS health. This research aims to know the description of the level of satisfaction of patients as a user of Health administrative enforcement against BPJS program JKN BPJS Health Hospital Umbu Rara Meha Waingapu. Methods: this study used descriptive method with a number of sample 50 people patients that are specified in the purposive sampling. Data were collected using a questionnaire.Results: aspects of the level of satisfaction include the aspect of Reliable (reliability) 78.5% satisfied, aspects of the Responsive (Responsiveness) 72.5% % satisfied, aspects of Assurance (Assurance) 71% satisfied, aspects of Empathy (Caring) 75.5% satisfied, and Tangible aspect (direct evidence) 75.5%. Conclusion: the majority of respondents (80%) feel satisfied while 20% are not satisfied against the enactment of the administration by the BPJS Health Hospital Umbu Rara Meha Waingapu.